STUDIES ON ADSORPTION AND CATALYTIC PROPERTIES OF STARCH FUNCTIONALIZED IRON OXIDE NANOPARTICLES - singh, Prakash narayan (iit bhu varanasi, 2016)
Please find the abstract in the attachement.
This thesis submitted by IIT BHU Varanasi, Phd scholar and supervised by Prof. Dhanesh Tiwary and Indrajit Sinha
Keywords: ADSORPTION AND CATALYTIC PROPERTIES OF STARCH; IRON OXIDE NANOPARTICLES